(untitled) (Journal of actual problems of jurisprudence, 2018)
The aim of the article is the definition, the role and the meaning of Maslihat as local representative agencies. In solving the questions and problems of complex and social development of the territories. The views and the result of investigation are analyzed of the history of building and development of the local government system in Kazakhstan, analyzing of its modem conditions and place and meaning of Malishat as central section of central government in complex development of the territory. The author investigated the constitutional legislation of Maslihat and made concrete offers of its improvement, in the article, the working experience of Maslihat and its deputies in decisions in such social problems as raising of pensions, building of roads and problems of under ages was shown. The ideals of the author can be used in law making process, in practicing activity of Malishat’s, in development of all parts of local government system and in the process of education on juridical faculties. Key words: Local self government, local representative agencies, complex social development of territory, social state, deputies of maslihats, problems of local meanings.